The Contribution Of Biomechanical Analysis Technology To Improve The Assessment Of Students During Certain School Sports Activities (Long Jump) - Guebli Abdelkader; Reguieg Madani; Sba Bouabdellah; Nurtekin Erkmen; Zerf Mohammed; Ekrem Boyali (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the contribution of biomechanical analysis technology to improve the assessment of students during certain school sports activities (long jump), this by (1) determining the statistical differences between groups in variables analyzed. (2) revealing the relationship between the kinematical variables analyzed and the digital level & evaluation result. The sample included 32 students in the 1st year of secondary school (16 males, 16 females), two groups for each gender. Group ? working on the use of kinetic analysis in a correction the kinetic performance and evaluated, and group ? is guided by the observation only. The study involved the kinematical analysis of performance during long jumping activity, by using the software; Coach's Eye & MyDartfish Express.  The data were analyzed in SPSS 22.0 program, the descriptive statistics (mean ± SD, Std. E), the Anova & T-tests for difference statistical between groups, and the P test for the correlations between variables. In conclusion, our assessment problem is that it depends on the digital level only in the learning phase. Besides, these results indicate that the professors who use this kinetic analysis software have adjusted the way they evaluate students, where Improving digital achievement should depend on proper evaluation in the stages of achievement for the physical education and sports teaching process.